Navigation Services to Avoid Rehospitalization among Medical/Surgical Patients with Comorbid Substance Use Disorder: Rationale and Design of a Randomized Controlled Trial. Issue 3 (2020) - Nordeck, Courtney D.; Welsh, Christopher; Schwartz, Robert P.
No abstract available